Kuseni Conjunction in Japanese Language - Elizabeth Ika Hesti Aprilia Nindia Rini; Vita Rahmadanti (IZUMI, 2020)
Kuseni is a a conjunction used to connect contradicting clauses which is called gyakusetsu no setsuzokushi in Japanese. This study aims to determine how the structure and meaning of kuseni conjunction is in Japanese sentences. The method used in this research is qualitative descriptive research. Kuseni is an adversative conjunction that connects contradictory clauses that contain criticism or reproach. Kuseni can be in the middle and at the end of a sentence, and can be attached to the class of verbs, nouns and adjectives in a sentence.